Review on Advances in Marine Diesel Engines and Its Impact on Ship Designs - Saeed, Khurram (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
The aim of this paper is to take full advantage of the waste heat which is being dissipated into the surrounding atmosphere from a diesel engine in which 25.5% by the exhaust gases, 14.1% and 6.3% by air cooler and jacket water correspondingly. A waste heat recovery system is used to recover exhaust energy, waste heat from the coolant system, and released heat from turbocharged air in the intercooler of a diesel engine. By using waste heat from the engines, the efficiency of the combustion process can be significantly improved, manufacturers claim that savings in fuel consumption and fuel costs can be up to 10%.Waste Heat Recovery System is one of the foremost energy reduction system to make a more efficient usage of fuels to achieve environmental improvement as well as saving the amount of energy which is being wasted from the Main engine power. The recovered energy of 11.4% is converted into mechanical energy to run the electrical generator to meet the power demands onboard ship and some part of the energy is being utilized on the steam service system, which ultimately is going to impact the designs of the ship.